An investigation into the use of thermal mass to improve comfort in British housing - Rodrigues, Lucélia Taranto (2010)
The UK Government has set ambitious targets for reducing energy use in buildings, including the target for all new homes to be zero-carbon by 2016. In addition, the government is committed to promote Modern Methods of Construction (MMC) as a solution for the shortage in housing that the country has been experiencing for a number of years. MMC have the potential to meet the new stricter building regulations and produce better quality homes that may use less energy for space heating but may also create homes that are more susceptible to overheating. Hence the paradox lies on the fact that a rising demand for cooling may be a result of the effort to reduce energy demand for heating.